Rehabilitation therapies for older clients of the Ontario home care system: Regional variation and client-level predictors of service provision - Armstrong, Joshua J.; Zhu, Mu; Hirdes, John P.; Stolee, Paul (Disability and Rehabilitation, 2015)
Purpose: To examine regional variation in service provision and identify the client characteristics associated with occupational therapy (OT) and physiotherapy (PT) services for older adults in the Ontario Home Care System. Methods: Secondary analyses of a provincial database containing comprehensive assessments (RAI-HC) linked with service utilization data from every older long-stay home care client in the system between 2005 and 2010 (n = 299 262). Hierarchical logistic regression models were used to model the dependent variables of OT and PT service use within 90 d of the initial assessment. Results: Regional differences accounted for 9% of the variation in PT service provision and 20% of OT service provision. After controlling for the differences across regions, the most powerful predictors of service provision were identified for both OT and PT. The most highly associated client characteristics related to PT service provision were hip fracture, impairments in activities of daily living/instrumental activities of daily living, cerebrovascular accidents, and cognitive impairment. For OT, hazards in the home environment was the most powerful predictor of future service provision. Conclusions: Where a client lived was an important determinant of service provision in Ontario, raising the possibility of inequities in access to rehabilitation services. Health care planners and policy makers should review current practices and make adjustments to meet the increasing and changing needs for rehabilitation therapies of the aging population. Implications for Rehabilitation 1. For older adults in home care, the goal of rehabilitation therapy services is to allow individuals to maintain or improve physical functioning, quality of life and overall independence while living within their community. 2. Previous research has demonstrated that a large proportion of home care clients specifically identified as having rehabilitation potential do not receive it. 3. This article used clinical assessment data to identify the predictors of and barriers to rehabilitation services for older adults in the Ontario Home Care System. Barriers of PT included dementia diagnosis and French as a first language. Barriers to OT included dementia diagnosis. 4. Policies and practices related to service provision for older adults should be reconsidered if we are going to meet the demands of aging populations and increasing rates of functional and cognitive impairments.

Le vieillissement des francophones de l’Ontario. Livre blanc - Assemblée de la francophonie de l’Ontario (2019)

White Paper on Ontario’s aging population - Assemblée de la francophonie de l’Ontario. (2019)

The health impact of living in a nursing home with a predominantly different spoken language: Lettor to the Editor - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes. Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services. French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones. However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored. We conducted a population-based retrospective cohort study to assess the impact of language discordance on hospitalizations, emergency department (ED) visits, and mortality in a cohort of 122,416 incident admissions to nursing homes in Ontario between 2010 and 2016.

L’offre active et l’accessibilité des services sociaux et de santé chez les personnes atteintes de démence en contexte francophone minoritaire - Bélair, Josée (Université d'Ottawa, 2019)
À l’heure actuelle, les besoins de soins de santé augmentent en réponse à la démographie vieillissante (Organisation mondiale de la santé, 2018). Pourtant, la difficulté d’accès aux services sociaux et de santé chez les usagers en situation minoritaire est une réalité présentée à l’aide de la littérature scientifique. En ce qui a trait aux populations minoritaires de la ville d’Ottawa, les études antérieures permettent de démontrer les obstacles touchant plus particulièrement les personnes francophones dans l’accessibilité des services sociaux et de santé (Kubina et collab., 2018). Dans le contexte de cette étude qualitative, le diagnostic de démence est pris en compte en tant que facteur explicatif de la difficulté accrue vécue chez les aînés francophones dans le recours aux services sociaux et de santé (Carbonneau et Drolet, 2014b). Un total de cinq proches aidants de la ville d’Ottawa a été recruté dans le but d’alimenter les objectifs de la recherche, c’est-à-dire : 1) d’identifier les barrières linguistiques dans la trajectoire des services sociaux et de santé ; 2) d’identifier l’influence des structures du Cadre d’analyse des leviers d’action pour l’accès et l’intégration des services sociaux et de santé pour les communautés de langue officielle en situation minoritaire (CALA) (Savard et collab., 2017) (Voir figure 1) dans l’accès aux services sociaux et de santé chez la population à l’étude. Quoique la majorité des participants à la recherche aient exprimé leur satisfaction par rapport aux services en français reçus pour leur proche atteint d’une démence, certaines barrières linguistiques telles que le manque de continuité dans les services en français ont été identifiées ainsi que le manque d’information quant à la disponibilité des services dans la communauté. De plus, la majorité des participants à la recherche ont pu identifier au moins un moment où les services à leur disponibilité étaient strictement en anglais. Bref, parmi les cinq proches aidants interviewés, quatre ont mentionné la nécessité de lutter pour l’obtention des services en français.

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)
In an exploratory study conducted on behalf of the Consortium national de formation en santé, a Canada-wide umbrella organization bringing together 11 postsecondary institutions that deliver training programs in various health disciplines in French, our research team explored the effect of language barriers perceived by elderly Francophone patients living in 3 different regions of Ontario with one or more chronic diseases. Our study was based on semistructured interviews of 25 elderly subjects (13 men and 12 women) with chronic diseases. It enabled us to determine the effect on the perception of the quality of care received by this Francophone population in relation to the challenges of language and literacy.

Impact de la situation linguistique minoritaire sur les soins de santé pour des personnes âgées francophones de l'Ontario souffrant de maladies chroniques : une étude qualitative exploratoire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Consortium national de formation en santé, 2010)

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)
Dans une étude exploratoire pour le compte du Consortium national de formation en santé, nous avons exploré l’impact des barrières linguistiques perçu par des personnes âgées francophones vivant en Ontario dans 3 régions différentes et souffrant d’une ou de plusieurs maladies chroniques. Notre étude, basée sur des entrevues semi-dirigées auprès de 25 personnes âgées (13 hommes et 12 femmes) souffrant de maladies chroniques, nous a permis de cerner des impacts particuliers sur la perception de la qualité des soins reçus par cette population en rapport aux enjeux de langue et de littératie.

La santé des personnes âgées francophones vivant en situation minoritaire au Canada : enjeux et besoins - Bouchard, Louise; Desmeules, Martin (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé L’objectif de ce chapitre est de présenter le profil sociodémographique et sanitaire de la population aînée francophone (65 ans et plus) vivant en situation linguistique minoritaire afin d’en ressortir les enjeux et les besoins qui la caractérisent. Nous aborderons dans un premier temps le fait minoritaire et son effet potentiel sur le vieillissement de la population et la position sociale des personnes âgées, leur santé et leur accès aux services. Une seconde section établira, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes (ESCC, cycles combinés, 2003-2012), le portrait sociosanitaire des aînés en fonction de trois grandes régions canadiennes (les provinces de l’Atlantique, l’Ontario et les provinces de l’Ouest). Enfin, nous discuterons ici de deux enjeux qui nous apparaissent fondamentaux au regard de cette population minoritaire, soit celui de la littératie en santé, c’est-à-dire la capacité de communiquer et de naviguer adéquatement dans le système de santé, et celui de l’offre active de services, une mesure d’équité et de qualité des soins. Mots-clés : aînés francophones, minorités linguistiques, portrait sociosanitaire, Canada, Enquête sur la santé dans les collectivités canadiennes (ESCC).

The health of Francophone seniors living in minority communities in Canada: Issues and needs - Bouchard, Louise; Desmeules, Martin (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter presents a profile of the socio-demographic characteristics and the health of Francophone seniors (aged 65 and above) living in minority language communities, and identifies the issues and the needs of this population. In the first section of the chapter, we discuss the minority context and its potential impact on the aging of the population, the social position of seniors, their health, and their access to services. The second section establishes the socio-sanitary profile of Francophone seniors in three large Canadian regions (Atlantic Canada, Ontario, and the West), based on data from the Canadian Community Health Survey—Annual Component (CCHS, combined cycles, 2003–2012). Finally, we discuss two issues that are, we believe, fundamental for this minority population: health literacy—the ability to adequately communicate in and navigate through the health system—and the active offer of services, which is a measure of equity and quality of care for people living in an official language minority community. Key Words: Francophone seniors, linguistic minorities, socio-sanitary portrait, Canada, Canadian Community Health Survey (CCHS).

Francophone seniors in Ontario: A health portrait - Bouchard, Louise; Makvandi, E.; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)

Les aînés francophones de l’Ontario : un portrait de santé. - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

The health of the Francophone population aged 65 and over in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Comment améliorer la santé des aînés francophones vieillissant en Ontario ? Entre approche populationnelle et santé communautaire - Bouchard, Louise; van Kemenade, Solange (La santé communautaire en 4 actes : repères, acteurs, démarches et défis, 2016)

La trajectoire des services sociaux et de santé d’aînés atteints d’une démence vivant en contexte francophone minoritaire : un engagement de multiples piliers durant une navigation complexe - Carbonneau, Corine; Drolet, Marie (Reflets, 2014)

Le recrutement et la rétention des professionnels de la santé et des services sociaux bilingues en situation minoritaire - de Moissac, Danielle; Savard, Sébastien; Ba, Halimatou; Zellama, Faïçal; Benoît, Josée; Giasson, Florette; Drolet, Marie (Université de Saint-Boniface et Université d'Ottawa, 2014)
Cete étude cherchait à connaitre les éléments favorisant l’engagement et la motivation des professionnels ainsi que les pratiques de gestion des ressources humaines qui encourage le personnel bilingue à s’intéresser au travail en milieu bilingue et à demeurer en poste.

Agir pour avoir accès à des services sociaux et de santé en français. Des francophones en situation minoritaire nous enseignent quoi faire! - Drolet, Marie; Arcand, Isabelle; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée (Revue canadienne de service social / Canadian Social Work Review, 2015)
Même si les droits des francophones de l’Ontario sont garantis par la Loi de 1986 sur les services en français, l’accès à des services sociaux et de santé en français dans cette province s’avère complexe en raison d’importantes barrières à recevoir de tels services sur un continuum. Nous avons exploré à l’aide d’entrevues qualitatives les points de vue de 40 parents et proches aidants francophones qui vivent en contexte bilingue dans la région d’Ottawa et dont l’enfant ou l’aîné pour lequel ils ont une responsabilité d’aidant utilise des services sociaux et de santé en français. Ces francophones s’avèrent des acteurs au sein de leur trajectoire de services, adoptant cinq stratégies pour accéder à de tels services. De plus, le sentiment de confort et la relation de confiance que procure l’usage du français tout au long de l’intervention, ainsi que le soutien des professionnels francophones ont facilité leur démarche. Il n’en demeure pas moins que l’offre de services en français ne doit pas devenir la responsabilité d’individus ou d’une minorité. Mots-clés : Francophonie en situation minoritaire, accès à des services sociaux, minorité linguistique, barrières aux services, offre active de services en français, entrevues qualitatives

Health services for linguistic minorities in a bilingual setting: Challenges for bilingual professionals - Drolet, Marie; Savard, Jacinthe; Benoît, Josée; Arcand, Isabelle; Savard, Sébastien; Lagacé, Josée; Lauzon, S.; Dubouloz, Claire-Jehanne (Qualitative Health Research, 2014)
We explore in this qualitative research the challenges faced by bilingual health and social services professionals in a Canadian bilingual setting, as well as the strategies used to overcome them. Eight focus groups were conducted with a total of 43 bilingual Francophone professionals who offered services in French in 21 health and social service organizations in eastern Ontario, Canada. We highlight linguistic issues affecting a minority Francophone clientele, the shortage of services in French, and organizational issues within these agencies. The solutions that the professionals adopt for better serving the clients and overcoming these challenges focus on adapting services from linguistic angles. In the long term, such an enhanced approach can affect staff well-being. Ensuring access to services for linguistic minority populations and the active offer of same should not rest solely on the shoulders of such professionals, but rather on organizational strategies.

L’expérience des francophones dans l’Est ontarien : importance des personnes pivots (usagers et intervenants) et influence des structures encadrant le système de santé et des services sociaux - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Le présent chapitre décrit l’expérience d’accès à des services sociaux et de santé en français de francophones de l’Est ontarien. Les expériences et les perspectives de 40 parents, aînés et proches aidants ont été recueillies à l’aide d’entrevues semi-structurées. Une analyse qualitative des verbatim ainsi qu’une analyse visuelle des trajectoires d’un sous-groupe de neuf participants ont permis de faire ressortir les facilitateurs et les défis d’accès aux services en français rencontrés par ces usagers, à partir de leur perspective ou de celle de leur proche aidant. Plus spécifiquement, ce chapitre met l’accent sur les éléments facilitateurs dans le but d’en tirer des leçons pour améliorer les services sociaux et de santé en langue officielle en situation minoritaire. Mots-clés : accès aux services en français, francophones Ontario, recherche qualitative.

The experience of Francophones in Eastern Ontario: The importance of key facilitators (service users and providers) and the influence of structures supporting the health and social services system - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter describes the experiences of Francophones in eastern Ontario in terms of access to social services and health care. The experiences and perspectives of 40 parents, seniors, and caregivers were collected through semi-structured interviews. Qualitative analysis of the transcripts, as well as visual analysis of the trajectories of a subgroup of nine participants, made it possible to identify facilitators and challenges these users experienced in accessing Frenchlanguage services, either from their perspective or that of their caregivers. More specifically, this chapter emphasizes elements that facilitate access; these are discussed in order to share the lessons learned, which can contribute to improvements in social services and health care in official language minority communities. Key Words: access to services in French, Ontario Francophones, qualitative analysis.

Comprendre l’expérience des femmes âgées en matière de l’accessibilité aux services sociaux et de santé en contexte francophone minoritaire [mémoire de maîtrise, Université d'Ottawa] - Dubuc, Vanessa (Université d'Ottawa, 2019)
Au Canada, les francophones en contexte minoritaire demeurent contraints au niveau de l’accès aux services sociaux et de santé en français en raison de barrières linguistiques. De plus, les femmes âgées en contexte francophone minoritaire sont sujettes aux inégalités vécues par les femmes âgées de façon générale, mais subissent également de la discrimination liée à leur statut de minorité. La présente recherche s’intéresse à l’expérience des femmes âgées en contexte francophone minoritaire en matière d’accessibilité aux services sociaux et de santé. De manière plus précise, cette recherche a pour but : 1) d’identifier les facilitateurs et les défis rencontrés par ces femmes ; 2) de comprendre la manière dont ces facilitateurs et ces défis ont des effets sur les différentes sphères de leur vie ; 3) examiner l’effet des structures institutionnelles et organisationnelles quant à l’accessibilité aux services sociaux et de santé de celles-ci. Afin de recueillir nos données, des entrevues semi-structurées ont été effectuées auprès de quatre participantes. L’analyse thématique des données, suivant un cadre théorique féministe intersectionnel, permet de mettre en évidence les éléments suivants selon les expériences des participantes : 1) l’accès aux services sociaux et de santé en contexte francophone minoritaire ; 2) la question du genre ; et 3) les réalités structurelles. Concrètement, les résultats indiquent que les participantes ont de la difficulté à accéder à des services sociaux et de santé dans leur langue, mais que le fait de s’identifier comme une femme ne semble pas jouer un rôle déterminant dans leur accès aux services en français. À la lumière des résultats, des recommandations sont proposées afin de mieux répondre aux besoins des groupes en situation linguistique minoritaire. Mots clés : francophone minoritaire, femme âgée, accès aux services sociaux et de santé, féminisme intersectionnel

Case studies: Primary health service delivery models for the Francophone minority - Entités de planification des services de santé en français 1 et 2(Érié St. Clair / Sud-Ouest et WaterlooWellington, Hamilton, Niagara, Haldimand Brant) Et le Réseau Franco - Santé du Sud de l’Ontario (2016)
In several regions of the province, Francophones are in a minority situation. In several places, health services in French are minimal or even non-existent. Many stakeholders are trying to find solutions to improve or implement health services in French. Often these solutions are not always easy to identify or put in place. In this context, the Erie St. Clair/SouthWest French Language Health Planning Entity has used the services of a consultant who did an analysis of best practices in minority situations across North America and in other countries. This first analysis consists of a brief description of 352 practices developed to meet the needs of minority populations receiving few, if any, health services in their communities. Following this report, we have continued this research jointly with the Waterloo Wellington, Hamilton, Niagara, Haldimand Brant Entity2 and the French Health Network of Central Southwestern Ontario. Our purpose was to be able to identify 5 or 6 best practices in minority situations that might be applicable in our respective regions under the subject areas: primary health care, seniors care, mental illness and chronic disease. Each of the partners could study identified practices and ask more detailed explanations on certain practices that seemed more appropriate to respond to their local needs.

Profil statistique 2011 – Personnes âgées francophones du Canada - Fédération des aînées et aînés francophones du Canada (2014)

Forum on Partnering for Innovative and Collaborative Long-Term Care Solutions for Francophones - Fondation Hélène Tremblay Lavoie Foundation; Reflet Salvéo (Fondation Hélène Tremblay Lavoie Foundation, 2019)
Access to French Language Services, more specifically to long term care beds and specialized dementia care units are not equitable and accessible across the Greater Toronto Area (GTA) and do not meet the specific needs of the Francophones in terms of location and language needs. Based on the goals of laying the foundation for action-oriented public / private / not-for-profit partnerships (social enterprise), better defining the needs of the Francophone community for specialized long-term care, and exploring innovative models that can be adapted to the different needs of the community, Fondation Hélène Tremblay Lavoie Foundation organized a one-day Forum to engage with different stakeholders on November 23, 2018 in Toronto. The one-day Forum ensured that key stakeholders, namely private/public sector, seniors, caregivers, health and social service providers, long-term care homes, retirement homes, financial institutions, developers and governments (LHINs, ministries, GTA municipalities), French Language Services Planning Entities (Reflet Salvéo and Entité 4) and post-secondary educational institutions such as Collège Boréal, Glendon, UOIT, York and Schulich and University of Toronto) came together to discuss on opportunities to - create an awareness of different programs and care models within the French community - facilitate access to and expansion of French health care services and programs for Francophone adults experiencing loss of autonomy - raise funds to support the improvement of long-term care and for an eventual capital project to support building the first bilingual long-term care facility dedicated to serving Francophone adults experiencing loss of autonomy within the GTA. This one-day engagement provided an opportunity for stakeholders the opportunity to make recommendations on moving forward. As such, 13 recommendations have developed for different stakeholders including the Francophone community.

La prise en compte de la langue dans les foyers de soins pour personnes âgées - Forgues, Éric; Gaucher, Charles; Guignard Noël, Josée; Kabano, John; Michaud, Jacques (Institut canadien de recherche sur les minorités linguistiques, 2012)

A guide for Planning and Providing Francophone Long-term Care Services - Learning from Pavillon Omer Deslauriers (POD) at Bendale Acres and Other Franch Language Health Services for Seniors in Canada - FRENCH HEALTH NETWORK OF CENTRAL SOUTHWESTERN ONTARIO (2017)

The pathway to diagnosis of dementia for Francophones living in a minority situation - Garcia, Linda J.; McCLeary, L.ynn; Emerson, Victor; Léopoldoff, Hélène; Dalziel, William; Drummond, Neil; Cohen, Carole; Koehn, Sharon; Silvius, James (The Gerontologist, 2014)
Purpose of the Study: As the prevalence of dementia increases, the pressure to make early diagnoses also increases. Although patients must be able to identify the symptoms to access appropriate services, they may not be equally accessible to all citizens in a multicultural society. Health care professionals and patients may lack a common “first language.” This study explores the experience of francophone persons with dementia (PWD) and their caregivers during the peri-diagnostic period. Design and Methods: Individual interviews were undertaken to elicit information regarding symptoms, the role of the family and friends, and the access to formal services. Seven PWD and their caregivers who spoke French as their primary language but who lived in a primarily English-speaking region completed the interviews. Results and Implications: No single symptom seemed sufficient to alert participants that dementia might be present. Participants communicated that there was a dire need to inform the public about the signs of dementia; they spoke of the role of the family physician and the importance of having a long-standing relationship with a health professional. For some, having similar personal characteristics, such as language and culture, might accentuate the strength of the relationship and facilitate the process of diagnosis.

Access to dementia services in a minority situation: The case of Francophones in Ontario [infographic] - Garcia, Linda; Chomienne, Marie-Hélène; Cadieux, M.-A.; Farmanova, E.; McCleary, L.; Molnar, F.; Agapitos, M.; Dalziel, W.; Khoury, L.; French-Merkley, V.; Joanisse, J. (2014)

Does end-of-life care differ for Anglophones and Francophones? A retrospective cohort study of decedents in Ontario, Canada - Guerin, Ewa; Batista, Ricardo; Hsu, Amy. T.; Gratton, Valérie; Chalifoux, Mathieu; Prud’homme, Denis; Tanuseputro, Peter (Journal of Palliative Medicine, 2018)
Background: Approximately half of decedents in Ontario, Canada, receive some palliative care, but little is known about the influence of language on the nature of these services. Objective: To examine differences between English- and French-speaking residents of Ontario in end-of-life care and outcomes (e.g., health care costs and location of death). Design: A retrospective cohort study using multiple linked databases. Setting/Subjects: A population-based cohort of decedents in Ontario (2010–2013) who were living in long-term care institutions (i.e., nursing homes) or receiving home care before death (N = 25,759). Data from two regions with higher representations of Francophones were examined, with the final distribution by primary language being 75% Anglophone, 18% Francophone, and 7% other languages. Results: Compared with Anglophones, Francophones were more frequent users of long-term care (47.6% vs. 37.1%) and less frequent users of home care (71.3% vs. 76.3%). In adjusted models, the number of days spent in hospital in the last 90 days of life was similar between Anglophones and Francophones, although the odds of dying in hospital were significantly higher among the latter. The mean total health care cost in the last year of life was slightly lower among French ($62,085) compared with English ($63,814) speakers. Conclusions: There are statistically significant differences in end-of-life outcomes between linguistic groups in Ontario, namely more institutionalization in long-term care, less home care use and more deaths in-hospital among Francophones (adjusted). Future research is needed to examine the cause of these differences. Strategies to ensure equitable access to quality end-of-life care are required.

Les bienfaits de la socialisation au programme de jour du Centre de services Guigues (CSG) sur la santé des personnes âges francophones ayant vécu l'isolement ou la solitude dans la région d'Ottawa - Kajuka, Dale (Université Laurentienne, 2017)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les trajectoires d'aînés dans le contexte de l'accès à des services sociaux et de santé en français dans la région d'Ottawa - Kubina, Lucy-Ann; Savard, Jacinthe; Drolet, Marie; Savard, Sébastien; Benoît, Josée (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2018)

Impact de la situation linguistique minoritaire sur les soins de santé pour les personnes âgées francophones de l’Ontario souffrant de maladies chroniques : partage des connaissances et rétroaction. Rapport de recherche - Lemonde, Manon; Boudreau, Françoise; Dufour, Suzanne (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Déterminants socio-économiques affectant le choix d’une maison de retraite : points de vue des résidents d’une maison francophone à Toronto [thèse de maîtrise, Université Laurentienne] - Maïna, Ali (2013)
Cette étude vise à explorer le problème de logement lié au vieillissement de la population. L’objet principal de la présente thèse est de comprendre les déterminants socioéconomiques qui influencent la décision des personnes âgées d’aller vivre en maison de retraite et leur choix d’une maison de retraite en particulier. Les données ont été collectées à l’aide d’une méthode qualitative, par l’entremise d’entrevues semi-directives. Les trente-sept personnes âgées constituant notre échantillon se sont exprimées sur leurs expériences afin de nous permettre de mieux cerner les déterminants socio-économiques affectant leur choix d’aller vivre en maison de retraite. Tous nos participants sont des résidents de la maison Héritage, une institution de Toronto. Les résultats de cette recherche nous révèlent que le choix d’aller vivre dans une maison comme l’Héritage implique des aspects qui dépassent largement les motifs purement économiques. En conséquence, les déterminants liés à la solitude, aux décès de conjoint (e), au soutien adapté, ont été très influents dans la première phase du choix d’aller vivre dans une maison de retraite. En revanche, dans le choix de l’Héritage, des déterminants liés à l’identité, comme la langue, les valeurs culturelles, ont été plus influents. Mots-clés déterminants socio-économiques, personnes âgées, maison de retraite, maison francophone (Héritage), langue, valeurs culturelles, financier

La prise en compte du français dans l’organisation des services en foyers de soins majoritairement anglophones au Canada - Michaud, Jacques; Forgues, Éric; Guignard Noël, Josée (Minorités linguistiques et société, 2015)
L’accès aux services de santé en français préoccupe grandement les communautés francophones vivant en situation minoritaire. Le présent article offre un survol de l’espace francophone dans les résidences collectives d’aînés du Nouveau-Brunswick, de la Nouvelle-Écosse et de l’Ontario à la lumière d’une recherche exploratoire menée en 2012. L’analyse des données obtenues auprès d’aînés, d’aidants et du personnel, l’examen de la répartition géographique des résidences et de la population d’aînés francophones, ainsi qu’un aperçu du contexte réglementaire encadrant le fonctionnement de ces résidences permettent de définir la problématique pertinente. Des actions en vue d’améliorer la situation sont examinées. Mots-clés : espace francophone, services de santé en français, francophones en situation minoritaire, foyers de soins, résidences collectives, vieillissement de la population

Enabling the participation of marginalized populations: Case studies from a health service organization in Ontario, Canada - Montesanti, Stephanie. R.; Abelson, Julia; Lavis, John. N.; Dunn, James. R. (Health Promotion International, 2017)
We examined efforts to engage marginalized populations in Ontario Community Health Centers (CHCs), which are primary health care organizations serving 74 high-risk communities. Qualitative case studies of community participation in four Ontario CHCs were carried out through key informant interviews with CHC staff to identify: (i) the approaches, strategies and methods used in participation initiatives aimed specifically at engaging marginalized populations in the planning of and decision making for health services; and (ii) the challenges and enablers for engaging these populations. The marginalized populations involved in the community participation initiatives studied included Low-German Speaking Mennonites in a rural town, newcomer immigrants and refugees in an urban downtown city, immigrant and francophone seniors in an inner city and refugee women in an inner city. Our analysis revealed that enabling the participation of marginalized populations requires CHCs to attend to the barriers experienced by marginalized populations that constrain their participation. Key informants outlined the features of a ‘community development approach’ that they rely on to address the barriers to marginalized peoples' involvement by strengthening their skills, abilities and leadership in capacity-building activities. The community development approach also shaped the participation methods that were used in the engagement process of CHCs. However, key informants also described the challenges of applying this approach, influenced by the cultural values of some groups, which shaped their willingness and motivation to participate. This study provides further insight into the approach, strategies and methods used in the engagement process to enable the participation of marginalized populations, which may be transferable to other health services settings.

Aînés francophones et intervenants multiethniques en santé : un projet de formation interculturelle adapté aux collègues francophones canadiens - Parent, R.; Bouchard, Louise; Lebel, M. (Reflets, 2014)

Cognitive health initiative for Francophone seniors in the GTA: Options fo Service Models - Reflet Salvéo; Entité 4 (2017)
Like the general population, the Francophone population is aging and at a faster rate than the population as a whole. While the median age for the Ontario population is 40.1 years, it is 44 for Francophones, and the largest age categories among Francophones are 45-54 and 65 and over: almost one out of five Francophones is included in these age groups. Although the population of the Central Region, including the Greater Toronto Area (GTA), is somewhat younger, the median age of Francophones is still higher than that of the Central Region population as a whole (41.1 vs 39.4) 4. Yet services for people with cognitive disorders and their families and caregivers are fragmented and do not necessarily meet their needs or the demand for service. The situation for those seeking services in French is even worse. Language and culture are key factors in providing quality, safe care. Language barriers constitute a major obstacle for people with dementia and their caregivers and families. Many Francophones lose their second language and revert to their mother tongue as they age, particularly when they are under stress; this is especially true for people coping with dementia. It is essential that Francophones with dementia and their caregivers have equitable access to a continuum of culturally sensitive quality care in French at every stage of the dementia journey. To meet the growing needs of the GTA’s aging Francophone population, the two French language health planning entities, Reflet Salvéo and Entité 4, have partnered on a feasibility study on cognitive health together with the five GTA LHINs (Central West, Mississauga Halton, Toronto Central, Central and Central East), Centres d’Accueil Héritage (CAH) and the Glendon Centre for Cognitive Health. The purpose of the study is to develop options for service models for memory services, including a memory clinic, focussing on very early detection and intervention for mild cognitive impairment but also addressing the need for referrals and supports for those farther along on the dementia journey, and their caregivers. The initiative will build on work previously done on memory centre services in French and on initiatives developed and implemented in the five GTA LHINs. The models proposed will align with LHIN and provincial strategic priorities for dementia and services for seniors and focus on helping people experiencing cognitive decline to remain active participants in their communities for as long as possible. Methodology The first step was a brief analysis of a previous literature review along with a number of studies, reports and plans dealing with the impact of dementia and current service models as well as provincial and LHIN strategic priorities and initiatives for the next several years. Research was also conducted into the availability of services for people with dementia and their caregivers both overall and in French. The next steps involved gaining an overview of existing models and opportunities. As a second stage, interviews were held with LHIN representatives to develop a picture of LHIN priorities and approaches to dementia services in a context of profound system transformation affecting home and community care, primary care and putting the focus on patients, including seniors. Subsequently, following development of a discussion guide, interviews were conducted with health service providers, both those serving the population as a whole and those identified to provide services in French. Another important step was seeking the voice of the Francophone community through a mixture of focus groups and online surveys. Once options are developed, we will go back to providers and the community to seek their input and validate our recommendations. Work on the project as a whole was overseen and supported by a steering committee that included representatives of the two French language health planning entities and the five GTA LHINs as well as the Glendon Centre for Cognitive Health and Centres d’Accueil Héritage (CAH).

Étude de besoins sur les foyers de soins de longue durée dans la région du nord-est de l’Ontario - Rapport intérimaire - Réseau du mieux-être francophone du Nord de l’Ontario (2017)
Au début de l’année 2016, le Réseau du mieux-être francophone du Nord de l’Ontario (RMEFNO) a obtenu des fonds afin de mener une étude de besoins sur les foyers de soins de longue durée dans la région du nord-est de l’Ontario. Cette étude, se concluant en mars 2018, a été divisée en deux parties. Ce rapport résume, pour la région du nord-est, les résultats de la première partie, suite à la collecte de données au sujet des francophones et des foyers de soins de longue durée du Nord de l’Ontario. Ce rapport traite des défis auxquels font face les francophones en situation minoritaire résidant dans un foyer de soins de longue durée. Puis, on y discute de soins culturellement adaptés, accompagnés d’exemples de meilleures pratiques tirées de foyers de soins de longue durée de la province. Finalement, des recommandations sont apportées quant aux foyers de soins de longue durée du nord-est. Ces recommandations touchent l’identification et la désignation sous la Loi des services en français, ainsi que les soins culturellement adaptés.

Needs Study: Long-Term Care Homes in the Northeastern Ontario Region - Interim report - Réseau du mieux-être francophone du Nord de l’Ontario (2017)
Early in 2016, the Réseau du mieux-être francophone du Nord de l’Ontario (RMEFNO) received funding to conduct a needs study regarding long-term care homes in the Northeastern Ontario Region. This two-part needs study is expected to be completed in March 2018. This report summarizes the results of Part 1, for the North East Region, based on the data collected on Francophones and long-term care homes in Northern Ontario. This report covers the challenges faced by Francophones in minority situations who reside in long-term care homes. As well, we touch on culturally appropriate care, and provide examples of best practices gathered from long-term care homes across the province. Finally, we make recommendations regarding long-term care homes in the North East. These recommendations address identification and designation under the French Language Services Act, as well as culturally appropriate care.

Guide de planification et de prestation des soins de longue durée en français. Leçons tirées du pavillon Omer Deslauriers de Bendale Acres et d'autres services de santé en français pour aînés au Canada - Réseau franco-santé du Sud de l’Ontario (2017)
pages: 106

Implementing the Optimal Model of Long-Term Care for Francophones and Other Cultural and Linguistic Minority Groups - Réseau franco-santé du Sud de l'Ontario and partners (2019)

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.

Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2019)
Le programme de Soins primaires communautaires pour aînés soutient les aînés et leurs proches aidants dans l’accès aux services sociaux et de santé requis (par exemple, la sécurité alimentaire, le logement, le revenu, le règlement, les services de soutien à domicile, le transport, l’éducation en matière des maladies chroniques, les activités sociales, physiques et récréatives). Un ou une gestionnaire de cas (soit un infirmier, infirmière ou un·e agen·te de santé communautaire) coordonne les services et les supports nécessaires et clarifie les rôles des fournisseurs de soins, facilitant ainsi la transition vers d’autres services. Il ou elle élabore, surveille et appuie la mise en œuvre des plans de soins coordonnés, et ce, dans un contexte de continuité relationnelle intervenant·e-client·e. Le service est offert en français et en anglais dans plusieurs centres de santé communautaires de la région d’Ottawa. Par la gestion de cas et la navigation des services, le programme facilite l’accès aux services en français qui existent.

Recruitment and retention of bilingual health and social service professionals in Francophone minority communities in Winnipeg and Ottawa - Savard, Sébastien; de Moissac, Danielle; Benoît, Josée; Ba, Halimatou; Zellama, F.; Giasson, Florette; Drolet, Marie (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
The difficulty in recruiting and retaining employees able to work in both official languages has been identified as one of the most significant reasons why Francophone seniors in minority language communities are unable to access social services and health care in French. This chapter presents the findings of a study of 55 profes sionals interviewed in six focus groups, who worked in bilingual organizations in one of the two regions studied (Winnipeg, Manitoba and Ottawa, Ontario). We hoped to identify the factors that led these employees to work in bilingual organizations and those that had encouraged them to stay in the organizations where they worked. Our findings show that the desire to contribute to the well-being of Francophones and the opportunity to obtain stable positions offering good working conditions are among the most important recruitment factors. The quality of the work environment and the opportunity to work in a diverse and inclusive workplace are retention factors mentioned regularly by the study participants. A greater recognition of the additional workload associated with working in both languages, and the recruitment of senior bilingual management staff, are among the recommendations proposed to improve the recruitment and retention of bilingual staff. Key Words: Recruitment and retention, social service and health professionals, Francophones in minority language communities.

Le recrutement et la rétention d’intervenants en santé et services sociaux bilingues en situation francophone minoritaire à Winnipeg et à Ottawa - Savard, Sébastien; de Moissac, Danielle; Benoît, Josée; Ba, Halimatou; Zellama, Faïçal; Giasson, Florette; Drolet, Marie (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
La difficulté à recruter des professionnels en mesure d’intervenir dans les deux langues officielles a été mentionnée comme une des causes les plus importantes du manque d’accès à des services sociaux et de santé en français pour les personnes âgées francophones en situation minoritaire. Ce chapitre présente les résultats d’une recherche réalisée auprès de 55 intervenants, rencontrés dans six groupes de discussion et travaillant dans des organisations bilingues dans deux régions, soit Winnipeg au Manitoba et Ottawa en Ontario. Nous voulions connaître les facteurs ayant incité ces intervenants à vouloir travailler dans des organisations bilingues et ceux favorisant leur rétention dans les organismes où ils travaillent. Les résultats démontrent que la volonté de contribuer au mieux-être des francophones et la possibilité d’obtenir des postes stables offrant des conditions de travail intéressantes font partie des facteurs de recrutement les plus importants. La qualité du climat de travail et la possibilité de travailler dans un milieu caractérisé par la diversité sont des facteurs de rétention mentionnés régulièrement par les participants à l’étude. Une meilleure reconnaissance du fardeau supplémentaire associé au fait de travailler dans les deux langues et le recrutement de cadres bilingues font partie de recommandations permettant de faciliter le recrutement et la rétention de personnel bilingue. Mots-clés : recrutement et rétention, intervenants services sociaux et de santé, francophones en situation minoritaire.

L’impact d’un programme éducatif sur la qualité de vie de personnes aînées autonomes et hypertendues en milieu francophone minoritaire [thèse de maîtrise, Université d'Ottawa] - Taillon, Myriam (2016)
L’hypertension artérielle est une maladie chronique qui affecte près de 50 % des personnes de plus de 65 ans au Canada et de façon disproportionnelle, les communautés en situation minoritaire linguistique. L’objectif du projet était de sensibiliser des personnes de 65 ans et plus, hypertendues, en milieu francophone minoritaire aux facteurs de risque de l’hypertension par des ateliers éducatifs. L’impact de ces ateliers a été mesuré par un questionnaire sur la qualité de vie et des groupes de discussion. Il y a eu 34 participants. Les questionnaires ont révélé une amélioration dans les dimensions physique et mentale de la santé des participants (p < 0,001). Les groupes de discussion ont démontré que les participants comprenaient mieux la maladie et avaient modifié certains comportements. Les ateliers ont été reconnus comme très positifs par les participants. En conclusion, ce programme éducatif de 3 mois est efficace, faisable et apprécié chez cette population. Mots-clés hypertension artérielle, haute pression, francophone en situation linguistique minoritaire, personnes aînées, prise en charge, programme éducatif